Adsorptive granulomonocytapheresis alters the gut bacterial microbiota in patients with active ulcerative colitis. Issue 3 (18th February 2021) - Chen, Xiuli; Lou, Lian; Tang, Haiying; Tan, Xiaoyan; Bi, Jian; Wu, Hao; Li, Na; Wang, Yingde; Mao, Jingwei
Abstract: Background: Ulcerative colitis (UC) is a refractory disease with unclear etiology. Studies have shown that UC is closely associated with gut microbiota dysbiosis. Adsorptive granulomonocytapheresis (GMA) using an Adacolumn has been found to treat UC effectively, but its underlying mechanism of treatment has not been fully elucidated. In this study, we aimed to investigate the influence of GMA on the gut microbiota in patients with active UC. Methods: We conducted a single‐center prospective analysis of patients with active UC who received GMA therapy and ultimately achieved clinical remission. Stool samples of healthy controls and patients before and after 5 or 10 sessions of GMA therapy were collected. Subsequently, high‐throughput sequencing of the 16S rRNA V3 and V4 gene region of the stool was conducted and clustering of operational taxonomic units and species annotation were performed. Results: Gut microbial profiles in patients with UC were characterized by low bacterial diversity. After 5 or 10 sessions of GMA therapy, the gut microbiota diversity in patients with UC increased and was similar to that of healthy controls. UC was further characterized by increased abundances of Proteobacteria and Bacteroides, as well as decreased abundances of Faecalibacterium, Roseburia, Firmicutes, and Dialister; however, after GMA therapy, the abundance of Bacteroides decreased, whereas those of Faecalibacterium, Roseburia, and Firmicutes increased. Conclusions: Active UC is associated with gut microbiota dysbiosis. GMA therapy exerts a strong regulatory effect on the gut microbiota in patients with UC.